“Dietary fibre”: moving beyond the “soluble/insoluble” classification for monogastric nutrition, with an emphasis on humans and pigs - Barbara A. Williams; Deirdre Mikkelsen; Bernadine M. Flanagan; Michael J. Gidley (Journal of Animal Science and Biotechnology, 2019)
Abstract This review describes dietary fibres originating from a range of foods, particularly in relation to their plant cell walls. It explores the categorization of dietary fibres into “soluble” or “insoluble”. It also emphasizes dietary fibre fermentability, in terms of describing how the gastro-intestinal tract (GIT) microbiota respond to a selection of fibres from these categories. Food is categorized into cereals, legumes, fruits and vegetables. Mention is also made of example whole foods and why differences in physico-chemical characteristics between “purified” and “non-purified” food components are important in terms of health. Lastly, recommendations are made as to how dietary fibre could be classified differently, in relation to its functionality in terms of fermentability, rather than only its solubility.